Brain structure characterization of huffaz (memorizers of the Quran): evidence from magnetic resonance imaging - Che Azemin, Mohd Zulfaezal; Jamaludin, Iqbal; Hassan, Radhiana; Sapuan, Abdul Halim; Mohd Tamrin, Mohd Izzuddin (2019)
The Government of Malaysia has developed various programmes to incorporate memorisation of the Quran among non-religious major students which include MRSM Ulul Albab and Darul Quran by JAKIM. However, to date, there is a lack of empirical evidence such programmes would induce change at the anatomical level especially in the brain. This study aims to characterise the structural change of the brain of the memorizers of the Quran (Huffaz). The existing technique to assess the brain structure suffers from the use of single feature and the extracted features require the analysis at binary level (black and white). However, the use of single feature and binarization of the image can remove subtle details. The objective of this study is to automatically characterize brain images using features extracted at the grayscale level. The expected outcomes of this research are the establishment of objective characteristics that can be used in the future to further understand the structural changes in brains exposed to extensive memorization regime and at the same time promoting al-Quran-based curricular in Malaysian education.